Power, Reliability, and Performance: One System to Rule them All. - Acun, Bilge; Langer, Akhil; Meneses, Esteban; Menon, Harshitha; Sarood, Osman; Totoni, Ehsan; Kale, Laxmikant V. (Computer (00189162), 2016)
In a design based on the Charm++ parallel programming framework, an adaptive runtime system dynamically interacts with a datacenter's resource manager to control power by intelligently scheduling jobs, reallocating resources, and reconfiguring hardware. It simultaneously manages reliability by cooling the system to the running application's optimal level and maintains performance through load balancing.